1998
DOI: 10.1021/ma971688b
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Nylon-6,6 Thermochemistry by Solid-State NMR

Abstract: Solid-state 13C and 15N NMR spectroscopy was used to study the structure and thermochemistry of nylon-6,6. Experiments were performed on samples of nylon-6,6 heated in the presence of labeled adipic acid and hexamethylenediamine (HMD) monomers as well as labeled bis(hexamethylenetriamine) (BHMT), a molecule previously implicated as a potential nylon cross-linker. The uptake and subsequent reaction of labeled materials were characterized by a variety of solid-state NMR techniques. Reaction of the central (α) ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This conclusion is also supported by the fact that Reaction (12) was the only one observed in PA 6, which in turn shows a much smaller tendency to form gel than PA 66 . Despite that, tertiary amides ( N , N ‐disubstituted amides, final product of Reaction12 and 13) have been detected for PA 66 as well as tertiary amines . Although tertiary amines can be generated for short residence times (≈3 h) in this medium (Reaction 11), they have been detected only under conditions of excess of amine groups.…”
Section: Assumptions and Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…This conclusion is also supported by the fact that Reaction (12) was the only one observed in PA 6, which in turn shows a much smaller tendency to form gel than PA 66 . Despite that, tertiary amides ( N , N ‐disubstituted amides, final product of Reaction12 and 13) have been detected for PA 66 as well as tertiary amines . Although tertiary amines can be generated for short residence times (≈3 h) in this medium (Reaction 11), they have been detected only under conditions of excess of amine groups.…”
Section: Assumptions and Modelingmentioning
confidence: 99%
“…These results motivated many researchers to interpret that the nitrogen of secondary amines (first step in Reaction (11–13) in Table ) act as the main branching point. Actually, Garbow et al demonstrated by 13 C NMR that the di‐substituted nitrogen of BHMT reacts rapidly to form tertiary amides (a branching structure) over the polymerization course (Reaction 12).Analogously, the same group performed other polymerization runs between 280 and 290 °C, as: (i) adding 5‐oxononane‐1,9‐dicarboxylic acid to PA 66, (ii) adding carboxyl groups in excess into a model compound, and finally, (iii) polymerizing PA 66 samples containing carboxyl at both ends (samples PA66COOH) . This procedure did not cause gelling in 3.5 h in the first case, gelled only after 35 h in the second case and did not form gel in the last one.…”
Section: Assumptions and Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in solid-state NMR of four different forms of isotactic poly(4-methyl-1-pentene) were explained by packing and conformational effects (161). Solid-state NMR was used to monitor thermochemistry of nylon-6,6 heated in the presence of labeled adipic acid and hexamethylenediamine (162).…”
Section: Synthetic Polymersmentioning
confidence: 99%